Nutritional, antioxidant and antitumour properties of Leccinum vulpinum Watling - Reis, Filipa S. (2014)
Mushrooms are widely appreciated all over the world for their nutritional [1] and bioactive properties [2, 3]. This work characterizes Leccinum vulpinum Watling, an edible mushroom harvested in Bragan<;:a's outskirts (Northeastern Portugal), a region with a great mycological biodiversity. The samples were chemically characterized regarding their content in nutrients and non-nutrients. Furthermore, the antioxidant and antitumour properties of the methanolic extract were evaluated. The nutritional value was assessed through the composition in macronutrients following standard procedures; the individual profiles in sugars, fatty acids, tocopherols, phenolic and organic acids were evaluated through chromatographic techniques. The antioxidant capacity was evaluated though the reducing power, radical-scavenging activity and lipid peroxidation inhibition of the samples. The screening for tumour cell growth inhibitory activity was carried out in four human tumour cell lines: AGS (gastric adenocarcinoma), MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and HCT-15 (colorectal adenocarcinoma). The activity of the extract was further studied in the most sensitive cells (HCT-15), particularly regarding its effects on the cell cycle profile (by flow cytometry). L. vulpinum species may be considered a healthy food, with a great nutritional value, being a source of nutraceuticals (e.g., mono- and polyunsaturated fatty acids, and vitamins) and other bioactive compounds (e.g., phenolic acids). This species also showed antioxidant activity. Concerning the antitumour properties, L. vulpinum inhibited the growth of the tested cell lines. Additionally, treatment of HCT-15 cells (the most sensitive cell line) with 77.2 flg/mL of this extract caused a statistically significant increase in the S phase and a decrease in the G2/M phase of the cell cycle.